Pregnancy rate obtained with four hormonal protocols for fixed-time artificial insemination in nulliparous water buffaloes (Bubalus bubalis) - Gallego, Carlos; Alonso, J. C; García López, R.; Padrón, E.; Fraga, L. M.; Méndez, Mildrer (Cuban Journal of Agricultural Science, 2016)
A total of 120 nulliparous water buffaloes were used to evaluate the effect of different hormonal protocols with fixedtime artificial insemination on the pregnancy rate. Protocol 1 received 2.0 mg of estradiol benzoate and a progesterone intravaginal device for nine days. After the device removal, 0.5 mg of Prostaglandin F2α, 500 UI of equine chorionic gonadotropin and 0.5 mg of estradiol cypionate were applied. Protocol 2 was similar to 1, but without the chorionic gonadotrophin. In protocol 3, two doses of 0.5 mg of Prostaglandin F2α were injected, with an interval of 11d, and 0.5 mg of estradiol cypionate was added to the last dose. Protocol 4 was similar to 3, but, after 48h of the last Prostaglandin F2α, 0.01 mg of Buserelin Acetate was injected. Time-fixed artificial inseminations were performed between 56 and 58 h (protocols 1, 2 and 3) and between 20 and 24 h (protocol 4) after the last hormonal application. Pregnancy rates in protocol 1 (60.8%), 2 (50. 3 %) and 4 (57.3 %) were superior (P<0.05) to those of protocol 3 (16.0 %). The equine chorionic gonadotrophin had no influence on the increase or decrease of fertility. In the protocol with double doses of Prostaglandin F2α and estradiol cypionate, fertility decreased, but increased when the estradiol was substituted by Buserelin Acetate. It can be concluded that protocols 1, 2 and 3 synchronize the estrum and ovulation with good pregnancy rates, and it is possible to apply fixed-time artificial insemination for increasing birth rate in herds and achieving economic benefits.Key words: hormonal protocols, fixed-time artificial insemination, nulliparous buffaloes